Overuse and Misuse of Antibiotics - Padma, K (Journal of Biomedical and Pharmaceutical Research, 2022)
The overuse of antibiotics — especially taking antibiotics even when they're not the appropriate treatment — promotes antibiotic resistance.According to the Centers for Disease Control and Prevention, up to one-third to one-half of antibiotic use in humans is unnecessary or inappropriate.Keywords: WHO, MDR